1993
DOI: 10.1038/361631a0
|View full text |Cite
|
Sign up to set email alerts
|

Landmark stability is a prerequisite for spatial but not discrimination learning

Abstract: Neurons sensitive to both place and direction from distinct regions of the hippocampal formation, allometric relationships between spatial learning and hippocampal structure and pronounced impairments in spatial learning after lesions in this area, indicate that the hippocampal formation subserves allocentric spatial learning. To learn more about the process of spatial representation, we have developed a task that provides independent control of both landmark and directional cues. On the basis of physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
3
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 17 publications
11
101
3
1
Order By: Relevance
“…That is, the effect of a visual landmark may depend on being initially experienced as stable relative to updatable egocentric representations and/or uncontrolled representations of the testing room (the cue is equally unstable across both sessions relative to visual snapshot representations). While we are not aware of experiments on landmark stability in humans, our results are consistent with previous experiments on rats in which the influence of landmarks on searching behaviour depends on their perceived stability (Biegler & Morris, 1993, 1996Lenck-Santini et al, 2002).…”
Section: The Effect Of the External Cue's Stabilitysupporting
confidence: 92%
See 2 more Smart Citations
“…That is, the effect of a visual landmark may depend on being initially experienced as stable relative to updatable egocentric representations and/or uncontrolled representations of the testing room (the cue is equally unstable across both sessions relative to visual snapshot representations). While we are not aware of experiments on landmark stability in humans, our results are consistent with previous experiments on rats in which the influence of landmarks on searching behaviour depends on their perceived stability (Biegler & Morris, 1993, 1996Lenck-Santini et al, 2002).…”
Section: The Effect Of the External Cue's Stabilitysupporting
confidence: 92%
“…Since the cue's stability relative to the subject's updatable egocentric representations may affect its influence on behaviour, the influence of a static visual cue might be reduced if the subject's internal sense of direction varies from trial-to-trial. This would explain the finding that when rats are systematically disoriented by spinning before each trial, their search is constrained only by the geometry of the environment, ignoring the visual cues within it (Cheng, 1986) unlike non-disoriented rats (Biegler & Morris, 1993, 1996Fenton et al, 1994;Lenck-Santini et al, 2002;Maurer & Derivaz, 2000;O'Keefe & Conway, 1980;Suzuki et al, 1980). It might also explain similar findings in the searching patterns of young children (Hermer & Spelke, 1994) and of adults performing verbal shadowing (Hermer-Vazquez et al, 1999), but cannot explain why non-shadowing adults do use visual landmarks despite having been disoriented.…”
Section: The Effect Of the External Cue's Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the hypothesis of allocentric spatial representations (Biegler & Morris, 1993;Nadel, 1991;Worden, 1992), several authors propose that place responses might be explained by mechanisms involving egocentrically referenced representations of landmarks. For example, it has been suggested that animals can be guided by stored information about the retinal size of each of several landmarks in the room, as viewed from the goal (Leonard & McNaughton, 1990;McNaughton, 1987).…”
Section: Use Of Allocentric and Egocentric Strategies As Revealed By mentioning
confidence: 99%
“…In conditions in which navigation has to be very precise, such as during the final approach to a goal, PI is too error-prone to be wholly relied upon, and so stable (Biegler and Morris, 1993), necessitating the use of external landmarks. During the outward journey to a known food source, foraging hamsters (Etienne, 2003), like ants (Collett and Collett, 2000), need external cues to stop at the goal site.…”
Section: Binding Of Landmark Information and Self-motion Cuesmentioning
confidence: 99%